Sosialisasi Tentang Pentingnya Internet Sehat Bagi Para Anggota OSIS SMK Fadilah Pondok Aren, Tangerang Selatan. - Leni Susanti; Dede Supriyadi; Imam Hidayat (AMMA : Jurnal Pengabdian Masyarakat, 2022)
OSIS is one of the legitimate organizations in schools. Therefore, every school has an OSIS institution consisting of students from the school itself. OSIS aims as a forum to achieve the goals of coaching and developing students in accordance with the school's vision and mission. Students who become OSIS members are teenagers who in their daily activities are always connected to the internet. The internet in the 21st-century era has changed the pattern of human life and culture in learning, working, communicating, shopping, and other aspects. The internet is the result of the development of technology and information that helps its users to access information from various sites easily and quickly. The Internet is a global communication network that connects computers and computer networks around the world. Not only computers, the current internet network can also be enjoyed by smartphone users. By using the internet, users can access any information without being limited by space and time. Fadilah Vocational High School is a vocational high school which is located at Jalan Pendidikan II, Parigi, Pondok Aren District, South Tangerang City, Banten 15227. The current ease of internet access not only has a positive impact on its users but also has a negative impact. Likewise, the information obtained is increasingly open to both positive and negative content. Various negative impacts caused by the internet such as addiction to playing online games, internet abuse such as gambling, opening porn sites, fraud, cyberbullying, copyright infringement such as spreading viruses, making teenagers lazy and rarely socializing, ignoring obligations to God Almighty, promiscuity, even perform data theft. With the intention of anticipating the negative impact of using the internet, Pamulang University lecturers held community service activities as a form of implementing the Tridharma of Higher Education. The target of this community service activity is more for the members of the Fadilah Vocational Student Council because the Fadilah Vocational Student Council members have an important role in developing the role of youth in conveying the positive and negative impacts of using the internet. So that the members of the Fadilah Vocational Student Council can continue the socialization of this healthy internet with their classmates, friends, and teachers who are in the school environment. After this outreach activity, the members of the Fadilah Vocational Student Council knew how to surf the internet properly, so as to minimize the negative impacts that would be caused. The output of this PKM activity is in the form of a journal that will be published nationally.